1992
DOI: 10.1002/hep.1840160502
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection in Medical Personnel After Needlestick Accident

Abstract: Hepatitis C virus infections in medical personnel after needlestick accidents have been documented generally by detection of seroconversion to a hepatitis C virus nonstructural region antigen, c100-3 (a marker of infection). We tested for hepatitis C virus core-derived antibodies and genomic RNA in addition to c100-3 antibody in 159 cases of needlestick exposure that did not involve patients positive for HBsAg. Of these we found 68 cases with index patients positive for both hepatitis C virus RNA and antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
11

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(109 citation statements)
references
References 25 publications
(16 reference statements)
2
96
0
11
Order By: Relevance
“…Between January 1998 and March 1999, 900 butterfly needles are known to have been ordered at the site. The probability of HIV, [8][9][10][11][12][13][14] HBV, [15][16][17] and HCV [18][19][20][21][22] infection following needlestick injury with contaminated blood was used as an estimate of the unknown transmission probability from needle reuse 4,5 (Table 1). We calculated a lower-bound estimate for the prevalence of each infection in the largely suburban clinic population by using National Health and Nutrition Examination Survey III (NHANES III) estimates [23][24][25] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Between January 1998 and March 1999, 900 butterfly needles are known to have been ordered at the site. The probability of HIV, [8][9][10][11][12][13][14] HBV, [15][16][17] and HCV [18][19][20][21][22] infection following needlestick injury with contaminated blood was used as an estimate of the unknown transmission probability from needle reuse 4,5 (Table 1). We calculated a lower-bound estimate for the prevalence of each infection in the largely suburban clinic population by using National Health and Nutrition Examination Survey III (NHANES III) estimates [23][24][25] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The risk factors for HCV transmission in the occupational setting are not well-defined. 11,12,13,14 During the past decade, the annual number of newly acquired HCV infections has ranged from an estimated 28,000 to 180,000. 15 Of these, an estimated 2-4 % occurred among healthcare personnel who were occupationally exposed to blood.…”
Section: Hepatitis Cmentioning
confidence: 99%
“…[1][2][3][4] Such infection may either transmit through percutaneous injuries or mucocutaneous exposure of blood or body fluids. [5][6][7][8][9] Studies showed that the percutaneous injury has the highest risk of transmitting infective pathogens, however there is also chance of transmission of infection via contact with skin or mucous membranes. [10][11][12] The incidence of HIV transmission through accidental exposure is 0.5% for needle stick injury with percutaneous hollow-bore needles and 0.1% for exposure to mucous membrane.…”
Section: Introductionmentioning
confidence: 99%